2020
DOI: 10.1371/journal.pone.0231357
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up and top-down effects on phytoplankton communities in two freshwater lakes

Abstract: The relative importance of bottom-up versus top-down effects in aquatic ecosystems remains a longstanding and ongoing controversy. To investigate these effects on phytoplankton communities in freshwater lakes, phytoplankton and zooplankton were sampled, and physical-chemical variables were measured during spring and summer in two important freshwater lakes in northern China: Nansi Lake and Dongping Lake. The redundancy analysis results showed that phytoplankton density and biomass were regulated by physicalche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 52 publications
2
21
0
1
Order By: Relevance
“…Similar findings have been reported in other African tropical lakes such as Lake Chad and Lake George, Lake Kariba (Talling 1986;Moyo 1991). As observed in other studies, the low temperature can lead to a decrease in zooplankton density in the Lake (Brucet et al 2010;Cremona et al 2020;Li et al 2020;Pomati et al 2020). In early HDS, Chl-a develops when nutrients are available and when temperatures are high.…”
Section: )supporting
confidence: 90%
See 1 more Smart Citation
“…Similar findings have been reported in other African tropical lakes such as Lake Chad and Lake George, Lake Kariba (Talling 1986;Moyo 1991). As observed in other studies, the low temperature can lead to a decrease in zooplankton density in the Lake (Brucet et al 2010;Cremona et al 2020;Li et al 2020;Pomati et al 2020). In early HDS, Chl-a develops when nutrients are available and when temperatures are high.…”
Section: )supporting
confidence: 90%
“…Hallegraeff (2010) suggested that phytoplankton is the primary producer in the complex food web system and this phytoplankton also produces Oxygen and organic matter through photosynthesis. This mechanism provides a better connection between primary producers with more advanced consumers in the food webs and provides a crucial link in the aquatic food web system (Li et al 2020). The changes in zooplankton density as seasonal changes are predominately influenced by physicalchemical (bottom-up effects) and predation (top-down effects) through the aquatic food web (Lv et al 2011;Muhid et al 2013;Li et al 2020).…”
Section: )mentioning
confidence: 99%
“…Other environmental variables (e.g., nutrients and pH) that were not investigated and so were not accounted for in the models could explain some of the variation. Biological impacts such as grazing and virus infection were also not taken into account but have previously been shown to have impacts on bacterioplankton communities ( Tijdens et al, 2008 ; Shurin et al, 2012 ; Li et al, 2020 ). Finally, the lakes in the study crossed multiple different environmental, chemical, and physical gradients and the interaction of these gradients may confound results.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike GR and SCR, which had small-dominant zooplankton assemblages, AR and CR contained higher abundances of large copepods and cladocera, which may explain the presence of planktivorous fish. In addition to connecting the planktonic food web to predatory fish, planktivorous fish can provide a top-down control on the plankton assemblage and density in lakes (Li et al, 2020 ). Predation by fish could explain why zooplankton abundance is relatively low in AR and CR despite high phytoplankton diversity in AR and abundance in CR.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found no correlation between biomass densities of phytoplankton or cyanobacteria and zooplankton, suggesting that the zooplankton population is not limited by food availability. Predation by planktivorous fish and carnivorous zooplankton is likely an important top-down control on zooplankton density that obscures the relationship between the phytoplankton and zooplankton communities (Sinstro, 2010 ; Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%